SURVIVE STRATEGY AND STRUGGLE OF MARAPU ADHERENTS IN TARUNG VILLAGE, WEST SUMBA - Ida Bagus Oka Wedasantara; A.A. Ngurah Anom Kumbara; I Nyoman Suarka (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2021)
Marapu is the indigenous religion of community in Tarung Village and Sumba Island in general. Marapu adherents experience hegemony including state discrimination and the spread of religion by the church elite. This study aims to reveal the hegemony process experienced and the survive strategies and struggles of Marapu adherents. Data were analyzed using hegemony theory and practice with qualitative research methods. The results showed Marapu adherents experience state hegemony in the aspect of their religious legality. This condition was used by church elite to spread their religion. The people of Tarung Village accept Christian/Catholicism, but still maintain the Marapu ideology as their religion, so that the reality that occurs in the local community is the practice of religious dualism as strategy of survive and negotiation. The struggle of Marapu followers continues after the Decision of Constitutional Court Number 97/PUU-XIV/2016 by trying to obtain a determination as Marapu customary law community. Keywords: Hegemony, Survive Strategy, Struggle, Marapu, Indigenous Religion